Sensitivity of Seismic Noise Correlation Functions to Global Noise Sources. Issue 8 (30th August 2018) - Sager, Korbinian; Boehm, Christian; Ermert, Laura; Krischer, Lion; Fichtner, Andreas
Abstract: Surface waves in seismic noise correlation functions are routinely exploited for tomographic studies. However, the observation and proper interpretation of body waves is considerably more difficult. To understand body wave generation in particular and the emergence of noise correlation signals in general, we investigate the sensitivity of correlation functions with respect to global noise sources. Treating noise correlation functions as self‐consistent observables, without the enforcement of Green function retrieval, enables us to investigate the quantitative contribution of different noise sources in space to a signal in a specific time window. The source sensitivity kernel for a surface wave reveals the expected dominant and broad region of stationary phase and thereby confirms the robustness of noise tomography in its current state. In contrast, kernels for potential body waves are highly oscillatory and indicate significant contributions from cross terms, for example, from body wave‐surface wave interactions. While the short‐wavelength nature of the body wave kernel may in the future allow us to infer noise sources with great detail, the importance of cross terms combined with the natural heterogeneity of noise sources renders an interpretation of such an arrival as a pure body wave almost impossible. Furthermore, we show that even long‐wavelength Earth structure significantly distorts sensitivity kernels. It is therefore essential to incorporate 3‐D heterogeneities into high‐resolution imaging of ambient noise sources, especially at higher frequencies. Key Points: We investigate the emergence of body and surface waves in noise correlations using finite‐frequency kernels In contrast to surface waves, earlier arrivals likely emerge from very localized noise sources Identifying arrivals as pure body waves is prone to misinterpretation due to contributions from different wave types